Azilsartan: Current Evidence and Perspectives in Management of Hypertension - Akshyaya Pradhan; Ashish Tiwari; Rishi Sethi (International Journal of Hypertension, 2019)
Hypertension continues to be global pandemic with huge mortality, morbidity, and financial burden on the health system. Unfortunately, most patients with hypertension would eventually require two or more drugs in combination to achieve their target blood pressure (BP). To this end, emergence of more potent antihypertensive drugs is a welcome sign. Angiotensin receptor blockers (ARBs) are cornerstones of hypertension management in daily practice. Among all ARBs, azilsartan is proven to be more potent in most of the head-to-head trials till date. Azilsartan is the latest ARB approved for hypertension with greater potency and minimal side effects. This review highlights the role of azilsartan in management of hypertension in the current era.